PENINGKATAN KEMAMPUAN MENULIS KARANGAN DESKRIPSI DENGAN MENGGUNAKAN PETA KONSEP BAGI SISWA KELAS IV SD NEGERI 07 NGALAU GADANG KECAMATAN IV NAGARI BAYANG UTARAPENINGKATAN KEMAMPUAN MENULIS KARANGAN DESKRIPSI DENGAN MENGGUNAKAN PETA KONSEP BAGI SISWA KELAS IV SD NEGERI 07 NGALAU GADANG KECAMATAN IV NAGARI BAYANG UTARA - ABU ZAHAR (FKIP UMSB, 2017)
This classroom action research conducted in order to improve the writing skills of elementary school students. Reality on the ground that applying conventional learning suspected cause saturation on students that negatively impact students' ability to write essays. The use of concept maps can enhance the ability of elementary school students write essays primarily in essay writing descriptions. Based on the results of research conducted in the fourth grade SDN 07 Ngalau Tower IV Nagari District of North Bayang, use of concept maps shown to increase students' ability to write the essay descriptions are concerned. Increased ability to write essays of this description can be seen from the quality of the resulting composition of students, both in terms of capitalization, punctuation, idea / ideas presented, and keruntutan phrases used.Keywords: Writing Narrative Description, Map Concept